Do case workers help the unemployed? - Michael Rosholm (IZA World of Labor, 2014)
Organisation for Economic Co-operation and Development countries spend, on average, an equivalent of 0.4% of their gross domestic product on active and passive labor market policies. This is a non-negligible sum, especially in times of strained government budgets. Meetings with case workersâwho can provide advice and information on what jobs to look for, and how to search, and give moral support, as well as monitor search intensityâare a simple and effective option for policymakers to help the unemployed find work.
Keywords: J64; J68; 330; unemployment; active labor market policies; effects of meetings; case workers